Strategies for Introducing Arabic Numbers and Colors in Early Childhood Education (PIAUD IAIN Kudus, 2025)
Arabic language learning for early childhood is often hindered by monotonous strategies, making it difficult for children to grasp the material effectively. This study describes the strategies used to introduce numbers and colours in Arabic at an early childhood education institution (RA) in Central Java. The research involved children from group A1 and a class 1 teacher as subjects. A qualitative approach was employed, with data collected through interviews, observations, and documentation. The findings indicate that the strategies used to introduce Arabic numbers and colors to young children involved memory, cognitive, and compensation strategies, combined with singing, conversation, and play methods. The integration of these strategies and methods enhanced the children’s engagement and attention in learning numbers 1–10 and basic colors in Arabic. Despite challenges such as limited facilities and children’s easily diverted attention, the learners remained enthusiastic, attentive, and showed cooperation in pronouncing numbers and colors in Arabic.